PENERAPAN MODEL PEMBELAJARAN DICOVERY LEARNING BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA MUATAN BAHASA INDONESIA KELAS VUPTD SD NEGERI 125 DATTE BOLA KABUPATEN ENREKANG - Musfirah Musfirah; Usman Usman; Ahmad Taufiq (ADIBA : JOURNAL OF EDUCATION, 2025)
This research is a class action research (PTK) which aims to determine the improvement of the learning process by applying the Discovery Learning learning model in Indonesian language learning about electronic advertisements of class V UPTD SD Negeri 125 Datte Bola Enrekang Regency and to determine the increase in learning motivation aided by wordwall media through cycles by applying the Discovery Learning learning model can increase the learning motivation of class V UPTD SD Negeri 125 Datte Bola Enrekang Regency. The approach used is a qualitative approach. The data collection techniques used were observation, questionnaire, and documentation. The research subjects were class teachers and students totalling 13 students and 1 teacher. The research was conducted in three cycles. In cycle I, the results of research on the learning process from the teacher aspect were in good qualifications (B) on the student aspect were in sufficient qualifications (C) and cycle I learning motivation was in sufficient qualifications (C). In cycle II the results of research on the learning process from the teacher aspect were in good qualifications (B), in the student aspect were in good qualifications (B) and cycle II learning motivation was in good qualifications (B). While in cycle III the results of research on the learning process from the teacher's aspect were in good qualifications (B), on the student aspect were in good qualifications (B), and cycle III learning motivation was in very good qualifications (SB). The conclusion of this study is that the application of the Discovery Learning model assisted by wordwall in Indonesian language content can improve the learning process and motivation of class V students of UPTD Negeri 125 Datte Bola, Enrekang Regency.